Pectin Extraction from Pineapple Peel and Its Aplication in Tomato Sauce as Thickening Agent - Cholidah, Nungky Rahmawati; Wicaksono, Dani Satrio; Septiyani , Lailatus Sa’diyah; Muflihati, Iffah; Suhendriani, Sari (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Pineapple production in Indonesia experienced a significant increase in 2021. Consequently, a proportional increase in pineapple peel waste was observed. Improper management of pineapple peel waste can lead to environmental pollution. However, this waste can be utilized to produce pectin, a complex polysaccharide with a high molecular weight. Pectin serves as a thickening agent in food products, including tomato sauce. This research aims to explore the potential of pineapple peel waste as a source of pectin and its application in tomato sauce production. The experimental design employed was a Completely Randomized Design (CRD) with four pineapple varieties as treatments: Honi, pineapple, local pineapple, and a mixture of the three. The procedure involved the extraction of pineapple peel powder using an acetic acid solution, resulting in pineapple peel pectin, and applied in the production of tomato sauce. The results indicated that the different pineapple varieties significantly influenced the pectin yield, sauce viscosity, sauce color, and sauce pH. The hedonic test revealed variations in the acceptance level among the tomato sauce samples with added pectin. Keyword : Pineapple peel, pectin, tomato sauce.